Hvor mange fraser er der i dansk? - Brink, Lars (HERMES - Journal of Language and Communication in Business, 2005)
It is my intention to put aside all tiresome discussions of phrase terminology, take the terminology of Brink 2004 for granted, and produce some new empirical facts about phrases, answering questions like: How many phrases are there in Danish – in total and with individuals? What is the numeric relation between idioms and collocations? Are idioms most often metaphorical? The investigation is a continuation of Brink 1979, and an updated version of the largest Danish dictionary is used as a base from which test samples are taken. Some statistical signiﬁcation tests are carried out with a favourable result.